Bilateral Oligopoly - Jonas Björnerstedt; Johan Stennek (The Research Institute of Industrial Economics (IUI), 2001)
In intermediate goods markets, both buyers and sellers normally have market power, and sales are based on bilaterally negotiated contracts specifying both price and quantity. In our model, pairs of buyers and sellers meet in bilateral but interdependent Rubinstein-Ståhl negotiations. The outcome has a simple characterization (a Nash equilibrium in Nash bargaining solutions) suitable for applied work. Equilibrium quantities are efficient regardless of concentration and also with few trading links. The law of one price does not hold. In addition to relation-specific characteristics, prices depend on both upstream and downstream concentration and on the structure of trading links. The requirements necessary for Walrasian prices are stronger than usually believed.
Keywords: C70; D20; D40; L10; L40; 330; Bilageral Oligopoly; Bargaining; Intermediate Goods; Decentralized Trade; Walrasian Outcome; Oligopol; Vorleistungen; Verhandlungstheorie; Theorie